IMPROVING THE QUALITY AND RELIABILITY OF SIGNAL TRANSMISSION AND RECEPTION IN MULTISERVICE NETWORKS» - Amreyev, М.; Yakubov, В.; Safin, R.; Yakubova, M. (Academic Scientific Journal of Computer Science, 2020)
This article describes the entire complete cycle of signal transmission and reception from the terminal device on the transmitting side to the terminal device on the receiving side, due to the fact that the reliability and quality of information transmission and reception in public access networks depend on many different parameters. The article describes the process of converting a signal from an analog form to a digital one. For this purpose, the so-called encoding of the graphic signal is used. To get a rich palette of colors, different intensities were set for the base colors. During the experiment, an IP video camera was used and digital traffic was prepared to transmit it over multiservice or open networks. The Novus IP video camera uses a web interface. During the initial installation, in order to access the camera interface, you must assign an IP address, subnet mask, and Ethernet adapter gateway to the PC. To ensure greater protection of information, it is necessary to apply encryption, which will increase the reliability of the process of transmitting and receiving information. Today, cryptography is one of the most used ways to ensure the confidentiality and authenticity of information. There are symmetric and asymmetric cryptosystems. In the symmetric encryption process, the same key is used for both encryption and decryption. Asymmetric systems use public and private keys that are mathematically related to each other. The DHCP-installer program was used and the distribution of IP addresses was obtained by agreeing to its terms. First, you need to configure the DHCP server. The DHCP Protocol is commonly used in most cases used in TCP/IP networks. In addition to the IP address, DHCP can also tell the client additional parameters that are necessary for normal network operation and these are called DHCP options. Today, there is a modern and high-speed Wi-Fi router that supports the wireless communication standard 802.11 a/b/g/n/ac. The router, in turn, transmits private information through any built-in interfaces. After high-speed transmission of traffic, the receiving side must perform the reverse encryption procedure-decryption, in order to get the original signal. As a result of the experiment on the equipment, we come to the conclusion that the studied parameters such as reliability, quality and secrecy of the transmitted information depend on the technical characteristics of the real equipment that was used in the experiment.